Mendelian randomization indicates causal effects of estradiol levels on kidney function in males - Nasr, M. Kamal; Schurmann, Claudia; Böttinger, Erwin P.; Teumer, Alexander (Frontiers in Endocrinology, 2023)
Context. Chronic kidney disease (CKD) is a public health burden worldwide. Epidemiological studies observed an association between sex hormones, including estradiol, and kidney function.Objective. We conducted a Mendelian randomization (MR) study to assess a possible causal effect of estradiol on kidney function in males and females.Design. We performed bi-directional two-sample MR using published genetic associations of serum estradiol in men (n=206,927) and women (n=229,966), and of kidney traits represented by estimated glomerular filtration rate (eGFR, n=567,460), urine albumin-to-creatinine ratio (UACR, n=547,361), and CKD (n=41,395 cases and n=439,303 controls) obtained from the CKDGen Consortium. Additionally, we conducted a genome-wide association study using UK Biobank data (n=11,798 men and n=6,835 women) to identify novel genetic associations with estradiol, and subsequently used these variants as instruments in a one-sample MR.Results. Two-sample MR indicated that genetically predicted estradiol levels are significantly associated with eGFR in men (beta = 0.077, P = 5.2E-05). We identified a single locus at chromosome 14 associated with estradiol levels in men being significant in the one-sample MR on eGFR (beta = 0.199, P = 0.017). We revealed significant results with eGFR in postmenopausal and with UACR in premenopausal women, which did not reach statistical significance in the sensitivity MR analyses. No causal effect of eGFR or UACR on estradiol was found.Conclusions. We conclude that serum estradiol levels may have a causal effect on kidney function. Our MR results provide starting points for studies to develop therapeutic strategies to reduce kidney disease.